Silica incorporated membrane for wastewater based filtration - Fernandes, C.S. (American Institute of Physics Inc., 2017)
Membrane technology has long been applied for waste water treatment industries due to its numerous advantages compared to other conventional processes. However, the biggest challenge in pressure driven membrane process is membrane fouling. Fouling decreases the productivity and efficiency of the filtration, reduces the lifespan of the membrane and reduces the overall efficiency of water treatment processes. In this study, a novel membrane material is developed for water filtration. The developed membrane incorporates silica nanoparticles mainly to improve its structural properties. Membranes with different loadings of silica nanoparticles were applied in this study. The result shows an increase in clean water permeability and filterability of the membrane for treating activated sludge, microalgae solution, secondary effluent and raw sewage as feed. Adding silica into the membrane matrix does not significantly alter contact angle and membrane pore size. We believe that silica acts as an effective pore forming agent that increases the number of pores without significantly altering the pore sizes. A higher number of small pores on the surface of the membrane could reduce membrane fouling because of a low specific loading imposed to individual pores. © 2017 Author(s).